(untitled) (Journal of Fiber Bioengineering and Informatics, 2019)
Research of flexible sensors for human wearable health monitoring are of paramount importance. In view of the problems of traditional sensors, such as complexity, low sensitivity, insufficient strain, short service life and incompatibility with human body, the research progress of Graphene-based flexible sensors in wearable health monitoring is systematically introduced. Benefitting from the commendable flexible mechanical properties and high durability, flexible Graphene-based sensors promote its applications in motion detection, body temperature monitoring, sweat ion real-time monitoring, voice recognition, pulsebeating, and respiration detection. The challenges and prospects of the application of Graphene-based flexible sensors in wearable health monitoring are pointed out. It is expected that most current research, which is still experimental, will need several more years of study before it becomes widely used. In the future, more attention should be paid to the lack of flexibility and high sensitivity of Graphene, the preparation of high purity Graphene, the application of composite materials and the development of advanced technology.